The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1001/jamapsychiatry.2018.2742
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Secondary Preventive Cardiovascular Treatment After Myocardial Infarction With Mortality Among Patients With Schizophrenia

Abstract: IMPORTANCE Cardioprotective medication use is an important secondary preventive treatment after cardiovascular events. Patients with schizophrenia have excess cardiovascular morbidity and mortality, but no studies have investigated whether taking recommended cardioprotective medication can reduce this excess mortality. OBJECTIVE To assess the association of exposure to secondary cardiovascular treatment with all-cause mortality after myocardial infarction among patients with schizophrenia compared with the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 32 publications
4
42
0
1
Order By: Relevance
“…For example, cardiac mortality in severe mental illness is significantly reduced by efficient administration of cardioprotective medications after first cardiac events. 356 This confirms assertions in new guidelines (See table 5) and Part 3 that dissemination of tertiary prevention measures in people with mental illness is often overlooked, despite their potential to improve health and reduce premature mortality.…”
Section: Lmic Implementationsupporting
confidence: 61%
See 1 more Smart Citation
“…For example, cardiac mortality in severe mental illness is significantly reduced by efficient administration of cardioprotective medications after first cardiac events. 356 This confirms assertions in new guidelines (See table 5) and Part 3 that dissemination of tertiary prevention measures in people with mental illness is often overlooked, despite their potential to improve health and reduce premature mortality.…”
Section: Lmic Implementationsupporting
confidence: 61%
“…126 However, contra-indications to specialized interventions, such as smoking or problems with informed consent, are less relevant to the prescription of vascular drugs such as ACE inhibitors, beta-blockers, or statins known to reduce subsequent morbidity and mortality. 127 Furthermore, recent data have shown that people with schizophrenia are equally adherent to diabetes medication as the general population, thus further supporting the need for healthcare providers to remain optimistic about prescribing cardiometabolic medications in people with mental illness. 128 Finally, access may be compromised by financial costs, fragmentation of care and stigma.…”
Section: Looking Beyond Lifestyle: Health Provider and System-level Fmentioning
confidence: 99%
“…Several studies have reported that patients with SMI receive less medical prophylaxis as well as fewer invasive procedures during hospitalization as compared to people without SMI . However, a recent observational study showed that exposure to secondary preventive cardiovascular treatment was associated with a reduced excess mortality in patients with schizophrenia . This association is not necessarily causal due to the risk of residual confounders, although it suggests that some interventions might work to reduce some of the excess mortality in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 97%
“…A Danish study [18] investigating the association between exposure to cardioprotective treatment after myocardial infarction and mortality rates, found that treatment decreased the mortality hazard rate (HR) ratio in patients diagnosed with schizophrenia from 8.87 to 1.97, and in the general population, lack of treatment increased the HR to 2.95 from 1 (reference value). At baseline, we found patients with schizophrenia to have almost double the prevalence of diabetes, COPD, and stroke, which corresponds to the values found in previous research [2,[18][19][20][21]. Over time, risk factors for ischemic heart disease, including diabetes mellitus, hypertension, and COPD, were also increasingly prevalent.…”
Section: Time Trends In Guideline-based Therapymentioning
confidence: 99%